2019
DOI: 10.3390/microorganisms7120629
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Antibody Prevalence and Risk Factors of Infection in the Human Population of Estonia

Abstract: Q fever is an emerging health problem in both humans and animals. To estimate the prevalence of Coxiella burnetii (C. burnetii) antibodies in the Estonian population, we analyzed plasma samples from 1000 individuals representing the general population and 556 individual serum samples from five population groups potentially at a higher risk (veterinary professionals, dairy cattle, beef cattle, and small ruminant stockbreeders and hunters). Additionally, 118 dairy cow bulk tank milk samples were analyzed to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
2
9
1
1
Order By: Relevance
“…The number of control group samples in the study was smaller than the number of risk group samples. Possibly, by increasing the number of control group samples tested, the results would be similar to the study in Estonia where 3.9% seroprevalence was detected among the general adult population, testing 1000 samples from the biobank of the Estonian Genome Centre (Neare et al, 2019).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The number of control group samples in the study was smaller than the number of risk group samples. Possibly, by increasing the number of control group samples tested, the results would be similar to the study in Estonia where 3.9% seroprevalence was detected among the general adult population, testing 1000 samples from the biobank of the Estonian Genome Centre (Neare et al, 2019).…”
Section: Discussionsupporting
confidence: 61%
“…However, the seroprevalence in the general population was 3.9% and it did not statistically differ from other risk groups -beef farmers, small ruminant farmers, and hunters. Statistically significant differences were not observed between genders and among various age groups (Neare et al, 2019). The observed seroprevalence in Latvia and Estonia is significantly lower than in other countries.…”
Section: Discussioncontrasting
confidence: 55%
“…Our results demonstrate that camels and their associated ticks in northern Kenya constitute an important epidemiological reservoir of C. burnetii , which increases human exposure and zoonotic risk of Q fever infection for camel-keeping communities, veterinarians and abattoir workers in the area. Antibodies against C. burnetii have been found in significant numbers of livestock handlers, indicating exposure to the pathogen [ 86 , 87 ]. Given the potential impact of C. burnetii on camel reproduction and the zoonotic risk for public health, further studies are required to better understand the role of camels in the epidemiology of Q fever.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study reported diverse seroprevalence for Q fever among the general population and high-risk groups like veterinarians and meat-processing workers (3% in healthy adults vs. 11–22% in high-risk occupations) [ 45 ]. Likewise, another recent study from Estonia [ 46 ] reported significantly higher seroprevalence of C . burnetii antibodies in veterinary professionals (9.62%) and dairy cattle farmers (7.73%) than in the general population (3.9%).…”
Section: Discussionmentioning
confidence: 86%